2022
DOI: 10.1002/ctpp.202200041
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism that drives electrostatic solitary waves to propagate in the Earth's magnetosphere and solar wind

Abstract: The origin of the solitary waves in the Earth's magnetosphere and the solar wind, particularly close to the magnetic reconnection (MR) regions, is still an open question. For that purpose, we used the fluid model to obtain the mechanism behind the formation of solitary waves in space plasmas with a variety of components. Our findings reveal that at the separatrix of the MR in the Earth's magnetotail, the counter-ejected electron beam leads to a broadening of the pulse amplitude. While increasing the electron b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In this section, we consider the propagation of non-linear IAWs in an unmagnified, collisionless plasma consisting of three components positive ions, proton beam and electrons which have Maxwellian distribution. Therefore, the dynamics of potential oscillations in our plasma is governed by the following normalised equations: for positive ions (Afify et al, 2022;Alotaibi et al, 2021)…”
Section: Governing Equations and Derivation Of Evolution Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we consider the propagation of non-linear IAWs in an unmagnified, collisionless plasma consisting of three components positive ions, proton beam and electrons which have Maxwellian distribution. Therefore, the dynamics of potential oscillations in our plasma is governed by the following normalised equations: for positive ions (Afify et al, 2022;Alotaibi et al, 2021)…”
Section: Governing Equations and Derivation Of Evolution Equationmentioning
confidence: 99%
“…With regard to plasma models discussed previously, the fluid constituent is usually composed largely of positive ions with few negative ions, which are treated as strictly hot. Likewise, some of the other models indicated that positive ions and superthermal electrons are abundant in the plasma regime (Yahia et al, 2021;Afify et al, 2022). Some theoretical studies that have focused on the large-amplitude slow electrostatic potential considered positive ions to be the coldest component, and negative ions to be the hottest, provided that the thermal rates of both types of ions are different (Mushinzimana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in laboratory experiments the scientists may control the conditions to produce certain wave. However, in the natural universe the perturbations appear and grow with no expecting what kind of wave evolution [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the profile of the solitary waves is observed to be affected by changing the plasma parameters. Moreover, the generation of electrostatic waves by counter electron beam in the Earth's magnetosphere and the observation of soliatry waves in the solar wind had been investigated [38].…”
Section: Introductionmentioning
confidence: 99%